2000
DOI: 10.1152/jn.2000.84.3.1240
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mechanism for Presynaptic Inhibition: GABAAReceptors Affect the Release Machinery

Abstract: Presynaptic inhibition is produced by increasing Cl(-) conductance, resulting in an action potential of a smaller amplitude at the excitatory axon terminals. This, in turn, reduces Ca(2+) entry to produce a smaller release. For this mechanism to operate, the "inhibitory" effect of shunting should last during the arrival of the "excitatory" action potential to its terminals, and to achieve that, the inhibitory action potential should precede the excitatory action potential. Using the crayfish neuromuscular prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…The silent presynaptic afferent terminals may become activated after their liberation from the shunting of action potentials at the terminals (Cattaert and El Manira, 1999;MacDermott et al, 1999;Parnas et al, 2000;Cattaert et al, 2001;Lee et al, 2002) or from the conduction block of action potentials by inhibitory transmitters at the branching points (Wall, 1995). This study has exhibited that such liberation from the shunting of presynaptic spiking might also underlie LTP.…”
Section: Ltp By Presynaptic Facilitationmentioning
confidence: 85%
“…The silent presynaptic afferent terminals may become activated after their liberation from the shunting of action potentials at the terminals (Cattaert and El Manira, 1999;MacDermott et al, 1999;Parnas et al, 2000;Cattaert et al, 2001;Lee et al, 2002) or from the conduction block of action potentials by inhibitory transmitters at the branching points (Wall, 1995). This study has exhibited that such liberation from the shunting of presynaptic spiking might also underlie LTP.…”
Section: Ltp By Presynaptic Facilitationmentioning
confidence: 85%
“…DA cells do contain GABA A receptors, uniformly distributed throughout their surface (30) as well as concentrated at the site of the synapses that DA cells receive from other GABAergic amacrines (23). Although examples exist in the literature of presynaptic inhibition mediated by presynaptic GABA A receptors (34,35), it seems unlikely that such receptors are concentrated at the release sites of the DA cell synapses. Finally, GABA A receptors are present in AII amacrine cells, because a Cl Ϫ conductance is activated in these neurons by muscimol, a GABA receptor agonist (36).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been reported that GABA A receptors also reduce neurotransmitter release by another mechanism that does not affect Ca 2? entry [35]. Hence, at present, mechanisms of the inhibitory effects of propofol and pentobarbital on the changes in [Ca 2? ]…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Richards [18] demonstrated that many general anesthetics inhibited the action potential-evoked secretion of neurotransmitter in the CNS and that their inhibitory actions could be fully accounted for by their Propofol and pentobarbital modulate GABA A -receptormediated inhibition in postsynaptic events [1][2][3][4][5][6][7]. GABA A receptors are also located on presynaptic boutons [13,14,[32][33][34][35]. These receptors reduce Ca 2?…”
Section: Discussionmentioning
confidence: 99%